Dental pulp stem cells in neuroregeneration - Sunil Paramel Mohan; Murugan Ramalingam (Wolters Kluwer Medknow Publications, 2020)
Neurological diseases and injuries affect the routine life of patients. Current medical and surgical treatment has not improved the quality of life to desired limits. Neural regeneration through stem cells may be ideal choice in current scenario. Dental pulp stem cells (DPSCs), which are isolated from dental pulp, have shown excellent neuroregenerative properties in various animal studies. This review outlines the clinical perspective of DPSCs in neuroregeneration.